Perancangan Model Perusahaan Industri Fashion Menggunakan Arsitektur Bisnis di Indonesia - Kevin Tjendrawinata (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Fashion industry is the second largest sub-sector in the Indonesian Creative Industry with contribution of 18.25% and the largest export in 2016 with a value of 54.54% from other Creative Industries. One of the challenges faced by companies engaged in the fashion industry is technology readiness by utilizing Cyber Physical Security (CPS) and Internet of Things (IoT). One of the common methods of utilizing CPS and IoT is the use of Big Data and Enterprise Architecture. This research is intended as a form of reference and a forerunner in the manufacture of corporate infrastructure and business models for companies engaged in the fashion industry. This research simulates creation process of a company, from the Business Model Canvas, Enterprise Architecture, and visualization using Archimate